FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2012)
Factors affecting the growth of the company is its financial structure, sales growth, the degree of operating leverage and financial risk of the company. This study aims to provide empirical evidence about the effect of financial structure, sales growth, the degree of operating leverage and financial risk to the company's growth by testing each variable. Objects in this study are Automotive companies listed in Indonesia Stock Exchange (BEI) from 2009 to 2011 and enrolled consecutively during the period of observation. While the population is employed manufacturing companies listed in Indonesia Stock Exchange. Sampling technique used was purposive sampling techniques that select objects based on certain criteria. Samples used from this study are a number of automotive companies 12 companies. The hypothesis assumed that the financial structure, sales growth, the degree of operating leverage, financial risk significantly affect the growth of the automotive companies listed in Indonesia Stock Exchange. The results of this study indicate that the financial structure, sales growth, the degree of operating leverage and financial risk has the ability to affect the growth of the company.